2016
DOI: 10.1159/000443765
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Rapidly Attenuates ORL-1 Receptor-Mediated Inhibition of Proopiomelanocortin Neurons via G<sub>q</sub>-Coupled, Membrane-Initiated Signaling

Abstract: Estradiol rapidly regulates the activity of arcuate nucleus (ARH) proopiomelanocortin (POMC) neurons that project to the medial preoptic nucleus (MPN) to regulate lordosis. Orphanin FQ/nociceptin (OFQ/N) acts via opioid receptor-like (ORL)-1 receptors to inhibit these POMC neurons. Therefore, we tested the hypothesis that estradiol excites POMC neurons by rapidly attenuating inhibitory ORL-1 signaling in these cells. Hypothalamic slices through the ARH were prepared from ovariectomized rats injected with Fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 70 publications
3
36
1
Order By: Relevance
“…Estradiol signaling rapidly induces neurotransmitter release [45, 8688] and regulates neurotransmission [89]. Indeed, estradiol (and steroid hormones in general) signaling through membrane receptors resembles GPCR neurotransmitter signaling [90].…”
Section: Membrane Estrogen Receptors Regulating Sexual Receptivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Estradiol signaling rapidly induces neurotransmitter release [45, 8688] and regulates neurotransmission [89]. Indeed, estradiol (and steroid hormones in general) signaling through membrane receptors resembles GPCR neurotransmitter signaling [90].…”
Section: Membrane Estrogen Receptors Regulating Sexual Receptivitymentioning
confidence: 99%
“…On the other hand, steroid treatments that induce sexual receptivity (estradiol, STX and PPT, an ERα agonist) have robust GIRK-1 currents, inhibiting β-end neurotransmission [108]. The decoupling of ORL-1 from GIRK-1 is mediated by activation of PLC/PKC/PKA and the phosphatidylinositol-3-kinase (PI3K)/neuronal nitric oxide synthase (nNOS) pathways [89; Fig 4]. …”
Section: Membrane Estrogen Receptors Regulating Sexual Receptivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is important in light of the fact that the cannabinoid regulation of energy homeostasis is sexually differentiated, with males being more sensitive to the hyperphagic and hypothermic effects than females. Moreover, estradiol further dampens the cannabinoid-induced hyperphagia, hypothermia, and presynaptic inhibition of glutamatergic input onto POMC neurons via the activation of estrogen receptor-α and the putative, G q -coupled membrane estrogen receptor, as well as the subsequent activation of phosphatidylinositol 3-kinase/neuronal nitric oxide synthase and phospholipase C/protein kinase C/protein kinase A pathways, respectively [for a review see 38, 39]. The hypothetical role of DAGL in the androgen-induced hyperphagia was presently affirmed by the fact that the DAGL inhibitor orlistat blocked the increase in energy intake caused by TP.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a truncated ER receptor variant, ER-α36 located on the plasma membrane discovered in 2005 (Wang et al 2005), is also reported to be involved in estrogen neuroprotection through rapid signaling of MAPK/ERK and phosphatidylinositol-3kinase (Han et al 2015). In addition, a Gq-coupled membrane ER (Gq-mER) exists which has a role in sexual behavior, and like ERα, rapid membrane initiated signaling triggers a signal transduction cascade involving phospholipase C, protein kinase C, protein kinase A, as well as phosphatidylinositol-3-kinase (Conde et al 2016). Moreover, crosstalk with classical ERs and GPER within the cell is postulated to modulate signaling in five different scenarios which complicates estrogen-meditated signaling even further (Hadjimarkou and Vasudevan 2017).…”
Section: Mechanisms Of Estrogen Neuroprotectionmentioning
confidence: 99%